Freeze-thaw stability of pickering emulsions stabilized by soy and whey protein particles. (August 2017) - Zhu, Xue-Feng; Zhang, Ning; Lin, Wei-Feng; Tang, Chuan-He
Abstract: The freeze-thaw stability of Pickering emulsions stabilized by (nano)particles from heated soy protein isolate (SPI) and whey protein (WP), was investigated and compared with those stabilized by unheated SPI (or WP) and sodium caseinate (NaCN). The stability was evaluated in terms of flocculation and coalescence degrees, and creaming index, as well as differential scanning calorimetry (DSC) characteristics. The emulsions exhibited different patterns of freeze-thaw stability, depending on the type of applied proteins, as well as the cycle number of freeze-thaw treatment. In general, the emulsions stabilized by heated SPI and WP exhibited much better freeze-thaw stability against coalescence and creaming, than those by unheated counterparts. The freeze-thaw stability against creaming of the heated SPI emulsion was even much better than that of the NaCN emulsion. The emulsions stabilized by SPI or WP, unheated or heated, showed poor freeze-thaw stability against flocculation. The differences in freeze-thaw stability between different emulsions could be explained in terms of the differences in physicochemical parameters of proteins or protein particles, as well as their microstructure. The good freeze-thaw stability of the emulsions by heated SPI and WP might be largely due to the action of Pickering steric stabilization, while the gel-like network formation also attributed to the stability. The results would be of great importance for the fabrication of Pickering emulsions stabilized by food protein particles and their applications in food formulations. Graphical abstract: Highlights: The freeze-thaw stability of soy or whey protein-based Pickering emulsions was investigated. The freeze-thaw stability of Pickering emulsions varied with the type of particles and stability items. The Pickering emulsions exhibited good freeze-thaw stability against coalescence and creaming. Soy protein Pickering emulsions exhibited a gel-like behavior related to droplet flocculation.